(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Spiritual intelligence is on of the effective factors in improving the quality of nursing services and can play a fundamental role in the observance of patients rights because it provides nurses to deal with stressful situations and situations. The quality of work life is a degree of nurses’ satisfaction with the level of individual’s important needs and organizational demands being met. Quality of work life is a factor beyond the level of job satisfaction and is related to the goodness of the people. Therefore, this research was designed and implemented to determine the relationship between spiritual intelligence and quality of work life in nurses in the oncology departments of Ahwaz hospitals in 2017. Methods: This descriptive correlational study was performed on 95 nurses in the oncology departments of Ahwaz hospitals. Sampling was done by census method. Data collection was carried out using personal data form, King’s Spiritual Intelligence Questionnaire and Richard Walton’s Quality of Work Life, whose validity has been proved in numerous studies. The reliability of the questionnaires was calculated by Cronbach’s alpha method. Cronbach’s alphas for the spiritual intelligence and quality of work life questionnaires were 9.33 and 0.93, respectively. Findings: The results of this study showed that most of the subjects were female, married, expert, passing the human resource plan, with a mean age of 30.06, an average work record of 5.44 ± 5.40 years, and with an average employment record in the oncology department equal to 3.65 ± 4.36 years. The results showed that the mean spiritual intelligence was 58.07% and the average quality of work life was 89.23%. Conclusion: Pearson correlation test showed that spiritual intelligence and quality of work life in nurses in oncology departments were significantly correlated, and the quality of work life has been increased with increasing spiritual intelligence in nurses (P = 0.016, r = 0.246). In examining the relationship between spiritual intelligence and individual characteristics in nursing staff, there was a significant relationship only between age, job history, and work experience in the oncology department and spiritual intelligence (P < 0.05). In examining the relationship between quality of work life and individual characteristics in nursing staff, there was a significant relationship only between job history and work experience in the oncology department and quality of work life (P < 0.05).